Mechanical characterization of PMMA by AFM nanoindentation and finite element simulation. (4th November 2016) - Zheng, L; Jiang, X; Deng, X H; Yin, J R; Jiang, Y; Zhang, P; Ding, Y H
Abstract: Atomic force microscopy (AFM) nanoindentation and finite element (FE) simulation were employed to investigate the nanoscale mechanical properties of PMMA at different temperatures. The elastic modulus and hardness of PMMA plate decreased with the increasing of ambient temperature. The residual depth was predicted by means of FE analysis of AFM nanoindentation. The effect of yield strength and tangent modulus on the residual depth was discussed.